THE EFFECT OF HYDROPHOBIC CALCINATION TEMPERATURE VARIATION OF SILICA / POLYSTYRENE COMPOSITE (SiO2 / PS) ON THE DURABILITY OF SELF CLEANING MATERIALS - Dila Juliawati; Ratnawulan Ratnawulan (PILLAR OF PHYSICS, 2021)
Nature possesses functional architectural and surface characteristics. The functional surface is one of the surfaces of taro or lotus leaves which has water-repellent (hydrophobic) properties. Water repellency is the ability to form on surfaces that escape from water (such as glass, ceramics, etc.). The purpose of this study was to determine the resistance of the surface layer on the SiO2/PS layer which is expected to be used for self-cleaning applications using calcination temperatures of 30oC, 60oC, 90oC, 140oC and 180oC for 1 hour using a furnace. This research is a type of experimental research conducted at the Material Physics Laboratory of FMIPA and the FMIPA Chemistry Laboratory, Universitas Negeri Padang (UNP). This study uses a HEM-3D (High Energy Milling Ellipse-3D Mention) tool. The precursor was made by giving the composition of 0.5 grams of polystyrene (PS)  and 0.2 grams of silica powder. Coating is done by using the spin coating method and giving the calcination temperature using a furnace. The results of this study were the variations in the calcination temperature of the SiO2 / PS composite hydrophobic on the resistance of the coating showed a change in the contact angle. Largest contact angles at temperatures of 60oC and for durability using contact angle tests with a distance of several days. The change in the contact angle decreases greatly, but the value of the contact angle is greatest at 60oC.